Theoretical problems in offences against property object vyâlenii - Atakhanova G.M. (Хабаршы. Заң сериясы, 2016)
This article discusses the theoretical aspects of offences against property to the object. The article reflects the development of theoretical provisions defining the concept, content, structure of the object of crimes against property, as well as defining the concept, characteristics and types of items of such crimes; in identifying areas to improve the criminal law and approaches to addressing skills related to the object and the subject of crimes against property.